Quality Control Analysis Using Statistical Quality Control (SQC) And Failure Mode Effect Analysis (FMEA) In The Production Process Of Za Plus Fertilizer - Ali, Syehan Habib; Widyaningrum, Dzakiyah (Universitas PGRI Semarang, 2024)
The company PT.XYZ is an industrial logistics entity that has a main division in the field of warehousing and MBU, with a special focus on fertilizer bagging activities. The problems faced by this company are related to defects that occur in the fertilizer bagging process. This research aims to identify the most common defects, the factors that cause defects, and develop proposed corrective actions to improve the quality of fertilizer bagging. The research methodology applied involves Statistical Quality Control (SQC) and Failure Mode Effect Analysis (FMEA), using tools such as check sheets, pareto diagrams, control maps, and fishbone diagrams. The results of the research using the Statistical Quality Control (SQC) method showed that the most significant defect in the fertilizer bagging process was the tear defect, reaching a percentage of 58%, followed by the seam defect at 27%, and the underweight defect at 15%. Meanwhile, analysis with the Failure Mode Effect Analysis (FMEA) method shows that the type of tear defect has the highest Risk Priority Number (RPN) value, caused by a lack of caution when carrying out the process of putting fertilizer into pallets. As a recommendation for improvement, it is recommended to organize training on work procedures for employees to improve their understanding of the work procedures that apply at PT.XYZ. This step is expected to address the main problems identified in the study, especially related to the lack of care in the process of bagging fertilizer into pallets, so as to improve the quality of fertilizer bagging in the company.